Religious intellectual humility, attitude change, and closeness following religious disagreement. Issue 2 (4th March 2019) - Rodriguez, Daniel; Hook, Joshua N.; Farrell, Jennifer E.; Mosher, David K.; Zhang, Hansong; Van Tongeren, Daryl R.; Davis, Don E.; Aten, Jamie D.; Hill, Peter C.
Abstract: This study explored the role of intellectual humility (IH) in promoting attitude change and relationship closeness in the context of religious disagreement. Participants ( N = 174) completed a preliminary survey that assessed their attitude on several contentious religious issues (e.g. gay marriage, abortion). Participants who disagreed about a contentious religious issue were then paired and engaged in a 10-min discussion. After the discussion, participants completed a series of questionnaires. The greatest degree of attitude change was seen in pairs with mutually high levels of IH, in which the participant self-reported high levels of IH and also perceived the discussion partner to have high levels of IH. Higher perceptions of the IH levels of the discussion partner predicted higher levels of closeness and trust. We discuss limitations, areas for future research, and practical implications.